Removal of faecal coliforms in facultative lagoon in the state of São Paulo (International Seven Journal of Multidisciplinary, 2023)
Pollution of water sources on the planet is a constant concern of society and should be widely discussed in the media as a whole. Faced with the reality of the precariousness of some countries in stimulating the conservation of water sources in their territory and in the problematic caused by the irregular distribution of surface water on the surface of the planet makes important the study of technologies for the treatment and conservation of water resources. Scientists, biologists and engineers around the world have been creating new ways to treat sewage so as to ensure the preservation of water. Among the technologies employed, we have adopted the stabilization pond system that creates an improvement in the water quality by the anaerobic and aerobic action present in the effluent itself when passing in large reservoirs designed for this purpose. The present study monitored and analyzed the removal of fecal coliforms present in the waters of the Capanema stream by a stabilization pond. The study lasted nine weeks and showed that from the Colilert coliform methodology, the pond system promoted a percentage clearance of 16.42% in relation to the amount of fecal coliform before treatment.